A multi-period logistics network design problem with transportation mode selection and outsourcing opportunities - Teresa Melo; Cortinhal, M.; Lopes, M. J. (OR2013, 2013)
We address the problem of redesigning a three-echelon logistics network comprising suppliers, plants, warehouses, and customer zones. To better cope with changes in customer demands, the geographic loca-tion of facilities (i.e. plants and warehouses), as well as their capacities, can be adjusted over a multi-period horizon. This involves opening new facilities at potential sites and selecting their capacities from a set of available discrete sizes. Capacity expansion may occur more than once over the planning horizon both at new locations and at existing facilities. The latter may also be closed. In addition, the operation of the network is subject to logistical decisions involving procurement, production, distribution, and outsourcing of goods. Multiple types of products can be manufactured at plants by processing given raw materials. The latter can be procured from various suppliers taking into account their availability and cost. Finished products can be shipped from plants to warehouses or directly to customer zones. Distribution channels are to be identified in each time period as well as the modes of transportation for raw materials and finished products. Warehouses may also purchase finished products from external sources at additional cost when the network faces insufficient production and/or storage capacity. We propose a mixed-integer linear pro-gramming model to redesign the network so as to minimize the total cost. Valid inequalities are developed to enhance the original formulation. For test instances of reasonable size, we report on our computational experience with standard mathematical optimization software. In particular, useful insights on the impact of various factors on network redesign decisions are provided.